The Microstrip Silicon Detector (MSD) data acquisition system architecture for the FOOT experiment. (1st March 2022) - Kanxheri, K.; Barbanera, M.; Ambrosi, G.; Silvestre, G.; Biondi, S.; Ridolfi, R.; Villa, M.; Aisa, D.; Caprai, M.; Ionica, M.; Placidi, P.; Servoli, L.; et al.
Abstract: The FOOT (FragmentatiOn Of Target) multi-detector experiment aims at improving the accuracy of oncological hadrontherapy for tumor treatment. It studies the nuclear fragmentation due to the interactions of charged particle beams with patient tissues employing the inverse kinematic approach to boost the fragments in the laboratory reference system. Hence it is necessary a tracking system in a magnetic field to measure the momentum of the charged fragments. The Microstrip Silicon Detector (MSD) is part of the charged-ions-tracking magnetic spectrometer for the evaluation of the Linear Energy Transfer LET (d E /d x ) and the nuclear fragments momentum. Here we describe the MSD architecture and its data acquisition system whose task is to collect and digitize the detectors output, generating a data packet to be sent to the experiment's central acquisition. This data acquisition system is designed and tested to withstand the trigger rate and detector's throughput; it has a small size and is easily portable, a necessary feature for an experiment that will move among the available ion beam accelerators and proton therapy treatment rooms.